Selective Intra-procedural AAA sac Embolization During EVAR Reduces the Rate of Type II Endoleak. Issue 5 (May 2016) - Mascoli, C.; Freyrie, A.; Gargiulo, M.; Gallitto, E.; Pini, R.; Faggioli, G.; Serra, C.; De Molo, C.; Stella, A.
Abstract : Objective: The pre-treatment presence of at least six efferent patent vessels (EPV) from the AAA sac and/or AAA thrombus volume ratio (VR%) <40% are considered to be positive predictive factors for persistent type II endoleak (ELIIp). The aim of the present study was to evaluate the effectiveness of sac embolization during EVAR in patients with pre-operative morphological risk factors (p-MRF) for ELIIp. Methods: Patients undergoing EVAR and intra-procedural AAA sac embolization (Group A, 2012–2013) were retrospectively selected and compared with a control group of patients with the same p-MRF, who underwent EVAR without intra-procedural sac embolization (Group B, 2008–2010). The presence of ELIIp was evaluated by duplex ultrasound at 0 and 6 months, and by contrast enhanced ultrasound at 12 months. The association between AAA diameter, age, COPD, smoking, anticoagulant therapy, and AAA sac embolization with ELIIp was evaluated using multiple logistic regression. The primary endpoint was the effectiveness of the intra-procedural AAA sac embolization for ELIIp prevention. Secondary endpoints were AAA sac evolution and freedom from ELIIp and embolization related re-interventions at 6–12 months. Results: Seventy patients were analyzed: 26 Group A and 44 Group B; the groups were homogeneous for clinical/morphological characteristics. In Group A the median number of coils positioned in AAA sac was 4.1 (IQR 1). There were no complications related to the embolization procedures. A significantly lower number of ELIIp was detected in Group A than in Group B (8/26 vs. 33/44, respectively, p  < .001) at discharge, and this was confirmed at 6–12 months (7/26 vs. 30/44 respectively, p  = .001, and 5/25 vs. 32/44, respectively, p  < .001). On multivariate analysis, intra-procedural AAA sac embolization was the only factor independently associated with freedom from ELIIp at 6 (OR 0.196, 95% CI 0.06–0.63; p  = .007) and 12 months (OR 0.098, 95% CI 0.02–0.35; p  < .001). No differences in median AAA sac diameter shrinkage were detected between the two groups at 6–12 months ( p  = .42 and p  = .58, respectively). Freedom from ELIIp related and embolization related re-interventions was 100% in both groups, at 6 and 12 months. Conclusion: Selective intra-procedural AAA sac embolization in patients with p-MRF is safe and could be an effective method to reduce ELIIp. Further studies are mandatory to support these results at long-term follow up.